1991
DOI: 10.1177/104438949107200303
|View full text |Cite
|
Sign up to set email alerts
|

Grandparents of Disabled Grandchildren: Hopes, Fears, and Adaptation

Abstract: The impact of childhood disability on grandparents has been largely ignored. The author reviews the roles and meanings of grandparenthood, then explores the potential impact of a disabled grandchild on grandparents. Ways in which grandparents can contribute to stress in the family or be a source of emotional and instrumental support are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 8 publications
0
28
0
1
Order By: Relevance
“…For their part, grandchildren offer their grandparents a new source of renewal and purpose in life and provide continuity of the family line and sense of immortality. People are becoming grandparents at a much younger age and continue in this role for longer periods than in the past Seligman, 1991) An exploratory study carried out by Nybo et al (1998) reported that 70% of people become grandparents in western society, with almost half under the age of 60. Grandparents also tend to be healthier, have living spouses, and are more affluent than grandparents in previous generations (Nybo et al, 1998;Smith, 1990).…”
Section: Grandparenthoodmentioning
confidence: 96%
See 3 more Smart Citations
“…For their part, grandchildren offer their grandparents a new source of renewal and purpose in life and provide continuity of the family line and sense of immortality. People are becoming grandparents at a much younger age and continue in this role for longer periods than in the past Seligman, 1991) An exploratory study carried out by Nybo et al (1998) reported that 70% of people become grandparents in western society, with almost half under the age of 60. Grandparents also tend to be healthier, have living spouses, and are more affluent than grandparents in previous generations (Nybo et al, 1998;Smith, 1990).…”
Section: Grandparenthoodmentioning
confidence: 96%
“…However, when the grandchild has a developmental disability, there will be additional stresses on the family system. The response of the grandparents to their adult child, their sons-or daughters-in-law, their healthy grandchildren as well as the grandchild with the disability, will have a significant influence on family dynamics and adaptation (Seligman, 1991).…”
Section: Grandparenthoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of flexibility can result in helplessness for residents, which negatively impacts affect and functioning (Seligman, 1991;Schultz et al, 1994), and causes frustration in staff members when residents 'do not perform according to their expectations'. The domains of flexibility and examples of flexibility issues for staff are outlined in Table 3.…”
Section: Flexibility/promoting Autonomymentioning
confidence: 97%